Características sociodemográficas, individuais e programáticas de mulheres com câncer de colo do útero - Conde, Carla Regiani [UNESP]; Lemos, Talita Mayara Rossi [UNESP]; Ferreira, Maria de Lourdes da Silva Marques [UNESP] (Servicio de Publicaciones de la Universidad de Murcia, 2018)
Introduction: cervical cancer is a serious public health problem throughout the world and often affects women of low socioeconomic level and of reproductive age. Objective: to identify the set of sociodemographic, individual and programmatic characteristics present in the daily life of women that made them vulnerable to cervical cancer. Method: descriptive and cross-sectional study addressing the various dimensions of vulnerability that had the participation of 99 women with a confirmed diagnosis of cervical cancer. To characterize the women, a structured questionnaire was used, composed of information directed to the sociodemographic aspects of the individual and related to the organization of the health services. Results: the predominant age group was between 40 and 57 years. Most started sexual activity between 15 and 18 years old, had up to five sexual partners and had never used a condom. There was prevalence of married, white, Catholic women with primary education, family income between one and two minimum wages and having their own house. Before the diagnosis of cervical cancer, 45.5% performed the preventive examination once a year and after cytopathological collection, it occurred at least once a year. The majority sought the health service after symptoms of the disease. Conclusion: it is necessary to develop effective interventions for women's health care based on the concept of comprehensiveness of care provided.
Sociodemographic, individual and programming characteristics of women with cervical cancer
Keywords: Uterine neoplasms; Vulnerability in health; Women's health